Method for producing Fe-Co-based coated alloy substrate, Fe-Co-based coated alloy substrate, and laminated core member
By forming a magnesium oxide film on the surface of the Fe-Co alloy substrate and optimizing the heat treatment conditions, the problems of regular embrittlement of the substrate and insufficient electrical insulation are solved, and the Fe-Co-based coated alloy substrate with high electrical insulation and good processability are achieved, and the performance of the laminated core member is improved.
Patent Information
- Application Number
- CN202380060654.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-06-16
- Publication Date
- 2025-03-28
AI Technical Summary
The heat treatment conditions of the existing Fe-Co alloy substrate when the surface film is formed are not optimized, resulting in regular embrittlement of the substrate, damaged processability, and difficult to obtain high electrical insulation.
By forming a magnesium oxide (MgO) film on the surface of the Fe-Co alloy substrate, and optimizing the heat treatment conditions, including setting an appropriate heating temperature and holding time, satisfying the conditional formula T×H/1000≦12.5, to form a MgO film of 0.4 μm to 2.0 μm.
While maintaining the substrate processability, it is possible to obtain a Fe-Co-based coated alloy substrate with high electrical insulation, thereby improving the manufacturing of the laminated core member and improving the performance of the rotary machine.
Smart Images

Figure CN119731372A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a Fe-Co based coated alloy substrate, a Fe-Co based coated alloy substrate and a laminated core member. Background Art
[0002] In recent years, from the perspective of protecting the global environment, the electrification of automobiles and aircraft has been actively studied, and the rotating machines carried therein are required to be further increased in output, miniaturized, and efficient. In order to achieve the high performance of such rotating machines, it is necessary to increase the saturation magnetic flux density of the magnetic components used as the core material of the rotating machine and to improve the iron loss characteristics.
[0003] As a general magnetic component for a rotating machine, an Fe-about 3 mass % Si alloy called a non-oriented electromagnetic steel sheet is used. However, as a magnetic component capable of obtaining a higher saturation magnetic flux density, an Fe—Co alloy called Permendur has been known.
[0004] Here, the magnetic component for a rotating machine is generally formed by processing the non-oriented electromagnetic steel sheet or the Permian alloy substrate into a component shape and stacking them together, but in order to reduce iron loss, it is necessary to improve the electrical insulation between the stacked substrates (hereinafter also simply described as insulation). For example, Patent Document 1 discloses a stacked core component stacked with a Fe-Co alloy substrate, and proposes forming a surface film of magnesium oxide, zirconium oxide, aluminum oxide, etc. as an insulating film on the surface of the substrate.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Publication No. 2012-521649 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The laminated core member for a rotating machine formed by laminating Fe-Co alloy substrates coated with a surface film disclosed in Patent Document 1 also has excellent electrical insulation between laminated substrates, which is effective for improving the performance of the rotating machine. On the other hand, when the heat treatment conditions for forming the surface film are not optimized, the embrittlement caused by the regularization of the Fe-Co alloy substrates impairs the processability or the handleability of the substrate when processed into a part shape by punching and the like, and when the film thickness of the surface film is thin, there is a concern that high electrical insulation cannot be obtained.
[0010] Therefore, an object of the present invention is to provide a method for producing a Fe-Co based alloy substrate having high electrical insulation on the substrate surface while maintaining the workability of the Fe-Co based alloy substrate, a Fe-Co based alloy substrate, and a laminated core member.
[0011] Technical means of solving problems
[0012] The present inventors investigated the relationship between heat treatment conditions and workability, and between the film thickness and electrical insulation when a surface film of magnesium oxide (hereinafter also referred to as MgO) is formed on the surface of an Fe-Co alloy substrate. As a result, it was found that high electrical insulation can be obtained without significantly impairing the workability of the Fe-Co coated alloy substrate by simply optimizing the heat treatment conditions and the film thickness of the MgO film, thereby achieving the present invention.
[0013] That is, one embodiment of the present invention is a method for manufacturing an Fe-Co based coated alloy substrate, characterized in that it includes: a step of coating a magnesium hydroxide solution on the surface of the Fe-Co based alloy substrate to form a liquid film; and a heat treatment step, wherein the heating holding time is set so that the coated substrate satisfies a temperature of 300° C. to 480° C. and satisfies the following conditional formula (1), and the heat treatment is performed to form a magnesium oxide film with a film thickness of 0.4 μm to 2.0 μm on the surface of the Fe-Co based alloy substrate.
[0014] Conditional expression (1): T×H / 1000≦12.5
[0015] Here, T is the heating holding time [min], and H is the heating temperature [°C].
[0016] Another embodiment of the present invention is a Fe-Co coated alloy substrate, wherein a magnesium oxide film is formed on the surface of the Fe-Co coated alloy substrate, wherein the total film thickness of the magnesium oxide film is 0.4 μm to 2.0 μm, and a test piece with a short side of 10 mm and a long side of 25 mm is collected from the coated alloy substrate. When a 90-degree bending test is repeatedly performed, the number of bending times until fracture occurs is more than three times.
[0017] Another embodiment of the present invention is a laminated core member formed by laminating the Fe—Co based coated alloy substrates.
[0018] Effects of the Invention
[0019] According to the present invention, it is possible to obtain an Fe-Co based coated alloy substrate having high electrical insulation on the substrate surface while maintaining workability and a high performance laminated core member. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] [ Figure 1] is a schematic diagram for illustrating the 90-degree bending test in this embodiment.
[0021] [ Figure 2 ] is another schematic diagram used to illustrate the 90-degree bending test in this embodiment. DETAILED DESCRIPTION
[0022] First, in the present invention, a Fe-Co alloy substrate is used as a magnetic component used as a core material of a rotating machine. The so-called Fe-Co alloy substrate of the present invention refers to a strip-shaped (coil) material or a rectangular thin plate (sheet). Moreover, the plate thickness of the Fe-Co alloy substrate of the present invention can be set to 0.5 μm or less, for example. The preferred plate thickness is 0.25 mm or less. Here, the so-called Fe-Co alloy in the present invention refers to an alloy material in which Fe+Co is more than 95% by mass% and contains 25% to 60% Co. The preferred lower limit of the Co amount is 40%. As a result, a high magnetic flux density can be exerted.
[0023] Next, the elements that may also be contained in the Fe-Co alloy of the present invention are described. In order to improve magnetic properties or cold workability, the Fe-Co alloy of the present invention may contain up to 5.0% of one or more elements of V, Si, Mn, Al, Zr, B, Ni, Ta, Nb, W, Ti, Mo, and Cr in mass %. For example, if it is V, it is preferably 1.0% to 3.0%. In addition, as impurity elements that are inevitably included, for example, C, S, P, and O can be listed, and for example, it is preferred to set the upper limit of each of them to 0.1%.
[0024] In the manufacturing method of the present invention, first, in order to form a film containing magnesium oxide (hereinafter also described as MgO) on the surface of the Fe-Co alloy substrate, a process (coating process) of applying a solution containing magnesium hydroxide (hereinafter also described as Mg(OH)2) to form a liquid film is performed. In addition, the reason for selecting MgO in the surface film is that MgO has excellent electrical insulation and thermal stability and tends to have lower hardness than other oxide layers. In addition, when magnetic annealing is performed to obtain the desired magnetic properties, the surface film is exposed to a hydrogen environment at a temperature of about 850°C, but MgO is not easily reduced by hydrogen, and the resistance to welding between the substrates is also excellent.
[0025] In the present invention, as a coating liquid for forming the film containing MgO, a Mg(OH)2 solution (hereinafter also referred to as slurry) is used, in which Mg(OH)2 powder, which is a precursor of MgO, is used as a solute and dispersed in a solvent. By using the slurry as a coating liquid, the slurry can be uniformly applied to the surface of the substrate with a stable film thickness. Mg(OH)2 used as a solute of the slurry is thermally decomposed by heating to become MgO, so that the MgO film can be easily formed. Here, magnesium carbonate (MgCO3) can also be used as a precursor other than Mg(OH)2. In addition, amphoteric solvents such as water and alcohol and organic solvents can be used as the solvent of the slurry. As a method for applying the slurry to a metal substrate, roller coating in which the slurry is applied to the substrate using a roller, dip coating in which the substrate is immersed in the slurry and then lifted up, or screen printing can be used. In addition, in order to improve the wettability of the substrate and the slurry, it is also possible to immerse the substrate in an alkaline solution or the like before applying the slurry, or to degrease the surface of the substrate based on discharge treatment or the like.
[0026] In the present invention, after coating, a heat treatment process is performed, wherein the heat treatment process sets the heating holding time and performs heat treatment in such a manner that the substrate coated with the slurry satisfies a temperature of 300°C or more and 480°C or less and satisfies the conditional formula "T×H / 1000≦12.5 (where T is the heating holding time [min] and H is the heating temperature [°C])" to form a MgO film on the substrate. In the case where the heat treatment process is performed at an insufficient heat treatment temperature and heating holding time, the coated Mg(OH)2 solution cannot completely become a MgO film and Mg(OH)2 remains in whole or in part, and there is a concern that electrical insulation is reduced or adhesion to the substrate is impaired. On the contrary, at an excessive heat treatment temperature and time, even if a complete MgO film is obtained, regularization of the Fe-Co alloy substrate will proceed, and there is a concern that the processability of the Fe-Co alloy substrate will be impaired. Therefore, in the present invention, the heat treatment is performed by setting the heating holding time so that the substrate coated with the slurry meets the temperature of 300°C or more and 480°C or less and satisfies the conditional formula "T×H / 1000≦12.5 (where T is the heating holding time [min] and H is the heating temperature [°C])". As a result, an Fe-Co based coated alloy substrate with excellent substrate processability and surface electrical insulation can be obtained.
[0027] Even if the conditional expression "T×H / 1000≦12.5 (T is the heating holding time [min], H is the heating temperature [°C])" is satisfied, when the heat treatment temperature is less than 300°C, a complete MgO film cannot be obtained and Mg(OH)2 remains in whole or in part. In addition, when the heat treatment temperature exceeds 480°C, or when the conditional expression "T×H / 1000" exceeds 12.5 even if the heat treatment temperature is 300°C or more and 480°C or less, the regularization of the Fe-Co alloy substrate proceeds, and there is a tendency that the workability of the Fe-Co alloy substrate is impaired. In addition, the preferred lower limit of the heat treatment temperature is 350°C, and more preferably 400°C. In addition, the preferred upper limit of the heat treatment temperature is 450°C. Furthermore, the conditional expression is preferably set to the range of "2.0≦T×H / 1000≦12.5", and more preferably set to the range of "2.0≦T×H / 1000≦5.0". For example, when the firing temperature is set to 450° C. and the heat treatment time is set to 10 minutes, T×H / 1000 is 4.5, which is within the range of the present invention.
[0028] The environment during the heat treatment in the manufacture method of the present invention is preferably an inert gas environment or a vacuum environment. The reason is that when firing in the atmosphere, the soft magnetic properties of the Fe-Co alloy substrate are prevented from being deteriorated due to excessive oxidation of the Fe-Co alloy substrate. The environment can be appropriately selected according to the equipment held or the desired characteristics. For example, in the case of desire to improve productivity, it is preferably set to an inert gas environment that can further improve productivity by continuously processing while passing a plate, and in the case of difficulty in the introduction of an inert gas environment device or in the case of desire to suppress cost, it is preferably set to a vacuum environment. As an inert gas environment, for example, a nitrogen environment or an Ar gas environment can be cited.
[0029] In the present invention, after the slurry is applied (coated) on the surface of the Fe-Co alloy substrate, a heat treatment is performed to form the MgO film, but a drying process for evaporating the solvent may be provided before the heat treatment. The drying process can be performed at a low temperature near the boiling point of the solvent, so the slurry can be dried quickly, and the liquid dripping that causes the uneven film thickness can be suppressed. In addition, since the drying process can be performed at a low temperature, there is also an advantage that the liquid film can be made into a dry film in the atmosphere.
[0030] Here, the film thickness of the MgO film formed on the surface of the Fe-Co alloy substrate of the present invention is 0.4 μm to 2.0 μm. The film thickness of the MgO film is correlated with the electrical insulation of the surface. By optimizing the film thickness by coordinating the MgO of the surface film, the electrical insulation of the surface can be improved. That is, when the film thickness of the MgO film formed on the surface of the substrate is less than 0.4 μm, in the MgO layer (the sum of the MgO film formed on the upper substrate + the MgO film formed on the lower substrate) formed between the soft magnetic components of the stacked core component (hereinafter also recorded as the stacked core component for the rotating machine) obtained by stacking the Fe-Co coated alloy substrate, high electrical insulation cannot be obtained. In addition, when the film thickness of the MgO film exceeds 2.0 μm, high electrical insulation can be obtained, but in the case of punching and punching the part shape from the substrate, in addition to the concern of impaired processability, the productivity of the Fe-Co coated alloy substrate is reduced. The lower limit of the thickness of the preferred MgO film is 0.5 μm, and the upper limit of the thickness of the preferred MgO film is 1.0 μm. In addition, the "thickness of the MgO film formed on the surface of the substrate" in the present invention means the total thickness of the MgO film formed on both sides of the substrate. Specifically, for example, a 0.2 μm MgO film is formed on the surface of the substrate, a 0.2 μm MgO film is formed on the back of the substrate, or a 0.4 μm MgO film is formed on the surface of the substrate, and a MgO film is not formed on the back. The object of the present invention is also formed. It is preferred to form an MgO film on both sides of the substrate. In addition, when the MgO film is formed on both sides of the substrate, the thickness of the MgO film formed on one side is 0.2 mm or more. In addition, the film thickness is preferably managed with a thickness of significant figures to the second decimal point, and more preferably, the film thickness of the MgO film formed on a single side is a film thickness of 0.40 μm or more. When the thickness of the MgO film formed on one surface is 0.40 μm or more and the total thickness of the film on the front and back surfaces is 0.60 μm or more, a 9.0×10 6 ( ) or above excellent sheet resistance (electrical insulation).
[0031] In addition, the Fe-Co based coated alloy substrate obtained by the manufacturing method of the present invention can suppress the regularization of the Fe-Co alloy substrate, so the number of bends until fracture occurs in the 90 degree bending test is 3 times or more, showing good processability. Figure 1 , Figure 2 2 is a schematic diagram of a 90-degree bending test apparatus according to the present embodiment. Figure 2 is from Figure 1Schematic diagram of observation in the A direction. In the 90-degree bending test in the present embodiment, a test piece 1 having a short side of 10 mm and a long side of 25 mm is clamped at right angles to the long side direction (rolling direction) by a clamping fixture 2a and a clamping fixture 2b having an edge chamfer width of less than 0.1 mm, and is subjected to repeated 90-degree bending, and the number of bends every 90 degrees until the test piece breaks is measured. In addition, the number of bends specified in the present invention is an average value, and specifically, it is sufficient to collect two test pieces for measurement and set the average value of the results obtained. In addition, the number of bends is the number of times the test piece is bent and the number of times the bent test piece is restored. For example, according to Figure 2 The bending test was carried out in the order of b1 (bending) → b2 (recovery) → b3 (bending in the direction opposite to b1) → b4 (recovery). When the test piece broke in the middle of b4, the number of bending times was counted as four.
[0032] The laminated core component for a rotating machine formed by using the Fe-Co-based coated alloy substrate can achieve high performance of the rotating machine due to the low iron loss caused by the high magnetic flux density of the substrate and the high electrical insulation of the surface. In addition, when the laminated core component for a rotating machine is actually manufactured, multiple sheets of the substrate of the present invention are stacked. At this time, when the MgO layer is formed on both sides (front and back) of the substrate, the thickness is the thickness of the MgO film formed on the back side of the upper substrate and the thickness of the MgO film formed on the surface side of the lower substrate when stacked. For example, if the substrates having a MgO film with a film thickness of 0.2 μm on both sides of the substrate are stacked, the thickness of the MgO layer formed between the substrates is 0.4 μm.
[0033] Example
[0034] (Example 1)
[0035] As the alloy substrate, a cold-rolled material (alloy substrate sheet) of an Fe-Co alloy shown in Table 1 was prepared. Then, after the prepared substrate was degreased with an alkaline solution, washed with water, and dried with hot air, a coating process was performed in which a liquid film of the slurry was formed on both surfaces of the substrate by dip coating in which the substrate was immersed in a slurry in which Mg(OH)2 particles as a solute were dispersed in water as a solvent and then lifted up.
[0036] The lifting speed of the dip coating was fixed at 1.2 mm / s. The substrate with the liquid film was treated in the atmosphere at a temperature of 110°C for a holding time of 5 min, and a drying process was performed to temporarily dry the liquid film. For the substrate after the liquid film was dried, a heat treatment temperature of 400°C to 600°C and a holding time of 5 min to 60 min were further performed in a nitrogen environment as a heat treatment process to obtain an Fe-Co-based coated alloy substrate having a MgO film with a thickness of 0.75 μm on both surfaces of the substrate.
[0037] Using X-ray diffraction (source CoKα), the MgO formation of the surface film after heat treatment is determined by the presence or absence of diffraction peaks on the (101) plane of Mg(OH)2 and the (200) plane of MgO, and the 90-degree bending test method is used to determine whether the substrate processability is good. Here, in the 90-degree bending test, a test piece with a short side of 10 mm and a long side of 25 mm is clamped at right angles to the long side direction (rolling direction) using a metal clamping fixture (chamfer width of 0.1 mm or less), and repeated bending of 90 degrees is performed to evaluate the number of bends per 90 degrees until the test piece breaks. In addition, in the 90-degree bending test, two test pieces are collected under each heat treatment condition for testing, and the heat treatment condition indicating an average of more than three bends is judged to be good. The results are shown in Table 2 (the value of "temperature × time" in Table 2 represents T×H / 1000).
[0038] [Table 1]
[0039]
[0040] [Table 2]
[0041]
[0042] According to the results in Table 2, regarding No. 2 to No. 4, No. 6, and No. 7, which are Fe-Co-based coated alloy substrates of the present invention, the disappearance of the diffraction peak in the (101) plane of Mg(OH)2 and the detection of the diffraction peak in the (200) plane of MgO confirm that the surface film is completely MgO-ized, and further confirms that the number of 90-degree bends is 3 to 5 times, and good workability of the Fe-Co alloy substrate is also obtained. In addition, it can be seen that condition No. 1, which is a comparative example deviating from the provisions of the present invention, is a state in which the liquid film after dip coating is dried, but the number of bends is 4.5 times and shows good workability. On the other hand, the diffraction peak in the (101) plane of Mg(OH)2 remains (the diffraction peak in the (200) plane of MgO is not detected), which is insufficient as a heat treatment condition. In addition, regarding Condition No. 5 and Condition No. 8 to Condition No. 17 as comparative examples, the disappearance of the diffraction peak in the (101) plane of Mg(OH)2 and the detection of the diffraction peak in the (200) plane of MgO were confirmed, but the number of 90-degree bends was 1 to 2.5 times, and it was speculated that the processability was greatly reduced due to the regularization of the Fe-Co alloy substrate, which was not suitable as a heat treatment condition.
[0043] (Example 2)
[0044] An alloy substrate sheet of an Fe-Co alloy as shown in Table 3 is prepared. After the prepared substrate is degreased with an alkaline solution, washed with water, and dried with hot air in the same manner as in Example 1, a liquid film of the slurry is formed on both surfaces of the substrate by dip coating, in which the substrate is immersed in a slurry prepared by dispersing Mg(OH)2 particles as a solute in water as a solvent and then lifted up.
[0045] The lifting speed of the dip coating was adjusted in the range of 0.02 mm / s to 1.20 mm / s to change the film thickness of the applied liquid film. After the liquid film was dried, the substrate was further subjected to a heat treatment in a nitrogen environment at a heat treatment temperature of 400°C or more (maximum reaching temperature 417°C) for a holding time of about 10 minutes. The value of conditional expression (1) was approximately 4.1.
[0046] Using a focused ion beam device (focused ion beam scanning electron microscope (FIB-SEM)), the film test piece for film thickness measurement is surface processed from a section in the thickness direction of the substrate at right angles to the rolling direction of the substrate, and the film thickness of the surface film (MgO) after heat treatment is measured using a transmission electron microscope (TEM). In addition, the electrical insulation of the surface film (MgO) after heat treatment is determined by measuring the sheet resistance (surface resistivity) of the surface using a four-terminal method based on a resistivity measuring machine. The results are shown in Table 4. Here, the film thickness shown in Table 4 represents the film thickness formed on one side of the substrate. In fact, since the MgO film is formed on both surfaces of the substrate, the total film thickness obtained by combining the film thickness on the surface side of the substrate and the film thickness on the back side is about twice the film thickness recorded in Table 4.
[0047] [Table 3]
[0048]
[0049] According to the results in Table 4, conditions No. 24 to No. 26 of the present invention examples, in which the film thickness on one side is 0.40 μm or more, have high sheet resistance (electrical insulation). In addition, for No. 24 to No. 26, the film thickness of MgO formed on one side is 0.40 μm or more, and the total film thickness of the front and back sides is 0.60 μm or more. In contrast, in the present invention examples No. 22 and No. 23, in which the film thickness on one side is less than 0.40 μm, a slight improvement in electrical insulation is observed compared to No. 18, which is a substrate without an MgO film on the surface. In addition, there is no significant difference in sheet resistance between the comparative example conditions No. 19 to No. 21 and No. 18, which is a substrate without an MgO film on the surface, and high electrical insulation is not shown.
[0050] In addition, in this embodiment, each sample is a coated alloy substrate sheet, but when it is actually used as a laminated core component for a rotating machine, it goes through a process of laminating multiple alloy substrate sheets. Since the MgO layer existing between the laminated substrates becomes the thickness obtained by adding the MgO layer formed on the upper substrate and the MgO layer formed on the lower substrate, if an alloy substrate sheet with a film thickness of 0.2 μm or more (total film thickness of 0.4 μm or more) on one side is formed on both sides of the substrate as in Conditions No. 22 and Conditions No. 23 of the present invention, the total thickness of the MgO layer existing between the substrates during lamination is 0.40 μm or more, and good electrical insulation can be expected. Moreover, as long as the film thickness is the conditions No. 24 to Condition No. 26 of the present invention, it can have a high sheet resistance (electrical insulation) even when the MgO film is formed only on one side.
[0051] In summary, the Fe—Co based coated alloy substrate obtained by the production method of the present invention has good processability and high electrical insulation, and can therefore contribute to improved manufacturability of the laminated core member and higher performance of the rotating machine.
[0052] [Table 4]
[0053]
[0054] Description of Figure Numbers
[0055] 1: Coated substrate
[0056] 2a, 2b: Clamping fixture
Claims
1. A method for producing a Fe-Co based coated alloy substrate, characterized in that: include: A coating step of coating a magnesium hydroxide solution on the surface of the Fe-Co alloy substrate to form a liquid film; as well as In the heat treatment step, the coated substrate is subjected to heat treatment for a set heating holding time so that the substrate satisfies the temperature of 300° C. to 480° C. and satisfies the following conditional formula (1), thereby forming a magnesium oxide film having a thickness of 0.4 μm to 2.0 μm on the surface of the Fe-Co alloy substrate. Conditional expression (1): T×H / 1000≦12.5 Here, T is the heating holding time [min], and H is the heating temperature [°C].
2. A Fe-Co alloy substrate having a magnesium oxide film formed on the surface of the Fe-Co alloy substrate, wherein: The thickness of the magnesium oxide film is 0.4 μm to 2.0 μm. A test piece having a short side of 10 mm and a long side of 25 mm was collected from the coated alloy substrate and subjected to repeated 90-degree bending tests. The number of bending times until fracture occurred was three or more.
3. A laminated core member formed by laminating the Fe-Co based coated alloy substrates according to claim 2.
Citation Information
Patent Citations
A laminated core made of soft magnetic material, and a method for joining single-layer core plates by the adhesive force forming the laminated soft magnetic core.
JP2012521649A